The Impact of Digital Promotion and Location on Consumer Loyalty with Customer Satisfaction as a Mediation Variable at Coffee Cart in Manado - Katiandagho, Oktavianus; Cahyono, Budhi (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The growth of mobile coffee carts in the digital era indicates significant potential within the coffee industry, particularly due to their location flexibility and low operational costs. This study primarily aims to identify the extent to which digital promotion and location factors influence customer loyalty toward mobile coffee businesses in the Manado area, with customer satisfaction considered as a mediating variable. The research adopts a quantitative approach with an explanatory design, involving 286 participants who provided data through a structured questionnaire. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The analysis results reveal that both digital promotion and location contribute positively and significantly to the development of customer loyalty. Their impact is not only direct but also indirect, as mediated by increased customer satisfaction. The findings underscore the importance of effective digital strategies, optimal location selection, and enhanced customer satisfaction as key factors in fostering loyalty within the mobile coffee cart sector. These insights offer valuable implications for MSME actors seeking to strengthen their competitiveness amid the intensifying landscape of the coffee business.